Immunotherapy for gliomas: shedding light on progress in preclinical and clinical development. (2nd July 2020) - Garcia-Fabiani, Maria B.; Ventosa, Maria; Comba, Andrea; Candolfi, Marianela; Nicola Candia, Alejandro J.; Alghamri, Mahmoud S.; Kadiyala, Padma; Carney, Stephen; Faisal, Syed M.; Schwendeman, Anna; Moon, James J.; Scheetz, Lindsay; et al.
ABSTRACT: Introduction: Gliomas are infiltrating brain tumors associated with high morbidity and mortality. Current standard of care includes radiation, chemotherapy, and surgical resection. Today, survival rates for malignant glioma patients remain dismal and unchanged for decades. The glioma microenvironment is highly immunosuppressive and consequently this has motivated the development of immunotherapies for counteracting this condition, enabling the immune cells within the tumor microenvironment to react against this tumor. Areas covered: The authors discuss immunotherapeutic strategies for glioma in phase-I/II clinical trials and illuminate their mechanisms of action, limitations, and key challenges. They also examine promising approaches under preclinical development. Expert opinion: In the last decade there has been an expansion in immune-mediated anti-cancer therapies. In the glioma field, sophisticated strategies have been successfully implemented in preclinical models. Unfortunately, clinical trials have not yet yielded consistent results for glioma patients. This could be attributed to our limited understanding of the complex immune cell infiltration and its interaction with the tumor cells, the selected time for treatment, the combination with other therapies and the route of administration of the agent. Applying these modalities to treat malignant glioma is challenging, but many new alternatives are emerging to by-pass these hurdles.